DIVORCE BEYOND THE COURT OF RELIGION FOR HIGHER EDUCATION (GRADUATE) - Yanti Yanti (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2020)
The background in this study is divorce outside the Religious Courts conducted by couples who have a history of higher education (bachelor). In-Law Number 1 of 1974 Article 39 and Compilation of Islamic Law Article 115 which states that "Divorce can only be carried out before a Religious Court hearing after the Religious Court has tried and failed to reconcile the two parties". The existence of these laws and regulations applies to all Indonesian citizens who are Muslim. Although it has been explicitly explained in the legislation regarding the necessity of divorce before a court hearing, in reality, the law is still ignored. Just like what happened in Renah Sungai Ipuh Village that the people in this village are still conducting divorce outside the court, from the data obtained by the author from 2013-2017 there were 24 couples who had divorced outside the Religious Court and 7 pairs of the perpetrators of the divorce were couples who have a high educational history (bachelor). The method used in this research is to use qualitative methods, namely analyzing the data that has been obtained. The conclusion of this research is first, that the causes of divorce outside the Religious Courts are 1. because they follow customs, 2. because they want to maintain their good name, 3. because of coercion from parents and 4. because the litigation process is too long and difficult. Second, the response of BP4 to the practice of divorce outside the Religious Courts, BP4 felt very concerned about the condition of the community who did not want to register their divorce in the Religious Courts, this BP4 has carried out its duties and functions to the maximum extent but has not been successful.